What role would the pores related to brittle minerals play in the process of oil migration and oil & water two-phase imbibition? - Guoxin Shi; Gen Kou; Shuheng Du; Yun Wei; Wei Zhou; Bo Zhou; Qiong Li; Bei Wang; Huiying Guo; Qingxiang Lou; Ting Li (Energy Reports, 2020)
This study aimed to investigate the geometry distinction of the pores formed by brittle minerals in shale oil reservoir and dig out its significance in hydrocarbon migration and exploitation. 14050 pores related to brittle minerals in typical shale oil reservoir samples are selected as the research objects, high-resolution field emission scanning electron microscopy (FE-SEM), imbibition test, Nuclear Magnetic Resonance(NMR), high-resolution image technique, construction of new parameters, statistics and analysis of large numbers and other means are used to discover this issue. Results firstly show that the development of pores in the two directions (Angle between two directions is 90 degrees or approximately 90 degrees) are complementary and promote each other. Reversely, the data points begin to be scattered, which means that the development of the pore in the above two directions begins to "lose stability", rather than promote each other all the time. This could prove that the rectangle (width, height), Legendre ellipse (major axis and major axis) and maximum and minimum Feret diameter of pores can all be used as the effective criteria for the development of pore shape related to brittle minerals. Sufficient evidences could prove that the pores related to brittle minerals contribute to oil and gas migration and oil & water imbibition. The conclusion of this study will provide an important theoretical basis for clarifying the oil occurrence mechanism of shale oil reservoir and looking for the geological and engineering dessert from the microscopic viewpoint.
Keywords: 330; Migration; Brittle minerals; Imbibition; Pore characterization; Shale oil